As healthy as invasive: Charybdis natator shell extract reveals beneficial metabolites with promising antioxidant and anti-inflammatory potentials - Galal-Khallaf, Asmaa; Samir Aboali, Esraa; El-Sayed Hassab El-Nabi, Sobhy; El-Tantawy, Ahmed I.; Schott, Eric J.; Mohammed-Geba, Khaled (Frontiers in Marine Science, 2024)
Crabs of the genus Charybdis are some of the world's most aggressive and voracious marine invasive crustaceans. They are found in a wide variety of ecosystems in the Red Sea. Their near ubiquity in diverse marine habitats, however, makes them a possible resource for novel marine-derived bioactive products. To provide an important insight into the potential for C. natator as a beneficial product, its shell methanolic extract was chromatographically analyzed for identification of potential bioactive ingredients. Additionally, two different doses, i.e. a low and a high dose, of this extract were tested for their ability to protect against copper-induced oxidative stress and proinflammatory response in adult zebrafish Danio rerio. Expression levels of transcripts of proinflammatory mediators, i.e. nfκβ and tnf-α; antioxidant enzymes, i.e sod, cat, and gpx; and lipid-metabolizing enzymes, i.e., acox1 and fasn, were determined. The results showed that C. natator shell is rich in potential bioactive metabolites, including diverse unsaturated fatty acids, alkanes, flavonoids, and phenolic acids. Most antioxidant and proinflammatory transcripts in the protected groups were restored to levels that were lower than those in the CuSO4-stressed group. The low dose showed special success in inducing these effects. Also, the low-dose-protected group showed significantly elevated acox1 and decreased fasn, suggesting the capability of crab shell extract at a low dose to assist lipolysis and inhibit lipogenesis. The abundant presence of saturated fatty acids in the shell extract can be the reason for the inadequacy of the high dose to preclude the antioxidant and anti-inflammatory activities. These results suggest that there is a potential to develop therapeutic industrial uses for C. natator shell, instead of considering it as a discard. Its wealth of bioactive metabolites may contribute to the market for natural products to combat inflammatory and oxidative stress, the origin of many diseases in the modern world.